Flight turbulence a time-series analysis on the influence of Philippine labor migration on economic growth - Rellosa, Reena Francesca DL
The economic impacts of labor mobility on countries of origin is an ongoing debate. Particularly in the Philippines, human capital flight has been increasingly seen as a means to escape unemployment concerns. This study aims to determine the influence that high skilled and low skilled migration has on the Philippines's economic growth and what it may imply for the country's economy. Using existing data gathered by the Commission on Filipino Overseas, the researchers identified the number of registered Filipino emigrants from 1988 to 2018 and segregated them into either high or low skilled workers based on their educational attainment prior to deployment. Multiple Linear Regression was then employed to establish the relationship between the explanatory variables and economic growth rate. Time series analysis is used to capture years of observation which could further aid in explaining how these factors can affect the economy. The results revealed that contrary to global studies, there is a positive association between the migration of highly skilled workers and the rate of economic growth, while results for low skilled migration showed a negative association with economic growth. Findings imply that high skilled emigration contributes to encouraging the youth to pursue higher education, increasing employment opportunities for domestic laborers, and stimulating consumption activities of the migrants' families through remittances. The deployment of low skilled workers, however, imply that the country may experience a shortage of low skilled labor supply in the short run, thus resulting in a fall of the Philippine economic growth rate.